Finding the right corporate legal strategy - Bird, Robert C.; Orozco, David (MIT, 2014)
Companies have increasingly recognized that legal capabilities are crucial for ongoing corporate success, and they understand the importance of working with legal counsel. All too often, though, senior executives still view the law as a constraint on managerial decisions, primarily perceiving it as an issue of cost and compliance. But this limited perspective of the law does not explain how some leading companies, such as Qualcomm and the Walt Disney Company, have managed to deploy their legal departments to shape the legal environment in order to secure long-term competitive advantage. In their research, the authors have developed a framework that can help executives identify the different ways in which legal strategies can be used to achieve various corporate goals, including the identification of value-creating opportunities. The framework consists of five different legal pathways, which the authors describe using examples such as Qualcomm, Microsoft, United Parcel Service and Xerox. In order of least to greatest strategic impact, the five legal pathways are (1) avoidance, (2) compliance, (3) prevention, (4) value and (5) transformation. In the avoidance pathway, managers see the law as an obstacle to their desired business goals. Companies operating in the avoidance pathway will often have lax internal controls or a failure to perform due diligence, and this approach can lead to disaster. Companies in the compliance pathway recognize that the law is an unwelcome but mandatory constraint, and they think of compliance basically as a cost that needs to be minimized. For businesses in the prevention pathway, managers take a more proactive approach, using the law to preempt future business-related risks. The value pathway represents a fundamental shift in mind-set, from risk management to value creation; managers use the law to craft strategies that increase ROI in ways that can be directly tied to a profit-and-loss statement. For companies in the transformation pathway, executives have integrated their legal strategy not only within the organization's various value-chain activities but also with the value chains of important external partners. Finding the right legal pathway for a particular company requires more than just a consideration of the overall business model. Other key factors include managers' attitudes toward the law and their level of legal knowledge, the sophistication of legal counsel and, in particular, the legal department's abil...
Includes bibliographical references. - Description based on online resource; title from cover page (Safari, viewed April 27, 2015)
Keywords: Corporation law; Corporate governance -- Law and legislation; Corporate governance; Law and legislation